DIAGNOSIS KESULITAN BELAJAR MATEMATIKA PADA POKOK BAHASAN BILANGAN BULAT NEGATIF PADA SISWA KELAS V DI SDN 108 BANOA - Triana, Suci; Nurjannah, Nurjannah (MEGA: Jurnal Pendidikan Matematika, 2023)
Difficulty in learning mathematics is an obstacle to problems in everyday life so it needs to be mastered well, but most students consider mathematics to be a difficult subject, especially fifth grade students at SDN 108 Banoa, the perception that mathematics is a difficult subject is reinforced by learning outcomes in mathematics which is still low. The purpose of this research is to identify difficulties in learning mathematics and the factors that cause difficulties in learning mathematics, especially for negative integers. Observations, interviews, and documentation are used as data collection methods in descriptive qualitative research. It uses triangulation to check the accuracy of the data and through the process of data collection, data presentation, and drawing conclusions, the data is analyzed. Based on the results of the study that students' learning difficulties in mathematics are still low, in this way the teacher must be more creative in choosing the learning method.